2013
DOI: 10.1016/j.cbi.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and oxidative DNA damage induced by climacostol–copper(II) complexes: Implications for anticancer properties

Abstract: Climacostol is a natural toxin isolated from the freshwater ciliated protozoan Climacostomum virens and belongs to the group of resorcinolic lipids. Climacostol exerts a potent antimicrobial activity against a panel of bacterial and fungal pathogens. In addition it inhibits the growth of tumor cell lines in a dose-dependent manner by inducing programmed cell death via intrinsic pathway. In this work, we investigated the possibility that climacostol exerts a prooxidant effect, inducing plasmid DNA strand breaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…These results demonstrate the pro-apoptotic effects of climacostol in melanoma cells, in agreement with previous results12. It has been shown that climacostol can effectively bind both histone protected and naked DNA, promoting their cleavage in the presence of copper(II)19. Our data revealed that climacostol triggers a Caspase 3-dependent apoptotic programme in melanomas with enzymatic degradation of DNA.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results demonstrate the pro-apoptotic effects of climacostol in melanoma cells, in agreement with previous results12. It has been shown that climacostol can effectively bind both histone protected and naked DNA, promoting their cleavage in the presence of copper(II)19. Our data revealed that climacostol triggers a Caspase 3-dependent apoptotic programme in melanomas with enzymatic degradation of DNA.…”
Section: Resultssupporting
confidence: 93%
“…Our data revealed that climacostol triggers a Caspase 3-dependent apoptotic programme in melanomas with enzymatic degradation of DNA. This enzymatic cleavage could reinforce the non-enzymatic one, thus playing an important role in explaining the preferential cytotoxicity of climacostol towards tumour cells that usually contain higher copper levels than normal cells19.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…from the geopolymer into fresh water also increased. Since oyster mushroom hyphae grow by absorbing nutrients from sawdust and water, the copper ions dissolved in the water suppressed the growth of oyster mushroom hyphae due to DNA damage [12][13][14][15].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Copper(II) ions exhibit strong antimicrobial activity [3][4][5][6][7][8][9][10][11] and can damage the DNA of organisms [12][13][14][15]. Therefore, materials that undergo a sustained release of copper ions have the potential to act as antimicrobial substances.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%